Following the Equator: A Journey Around the World. Part 3 - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Following the Equator: A Journey Around the World. Part 3" by Mark Twain is a travelogue published in 1897. Facing near bankruptcy, Twain embarked on a lecture tour through the British Empire at age sixty. This account blends perceptive observations of cultures, customs, politics, and landscapes with sharp social commentary delivered in Twain's characteristic satirical style. The work notably weaves fictional stories into its non-fiction framework, blurring the lines between travel journalism and creative storytelling. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Following_the_Equator
Release date is 2004-06-23
Produced by David Widger
Keywords: Voyages around the world; Twain, Mark, 1835-1910 -- Travel; Equator -- Description and travel